Improving Awareness and Screening of Obstructive Lung Disease in Post-Tuberculosis Patients: A Community Service Program at Depok - Ananda, Fannie Rizki (Indonesian Society of Respirology (ISR), 2026)
Background: Post-tuberculosis lung disease (PTLD) is a rising public health concern despite the urgency of eliminating the active infections of tuberculosis (TB). Even after successful treatment, almost half of patients continue to have limitations related to respiratory complaints, particularly dyspnea and chronic cough. This has resulted from airway and parenchymal destruction. This study was conducted as a community service program at Bhakti Yudha Hospital, Depok, to provide education and early screening of respiratory disorders in post-TB patients. Method: This study consisted of material presentations on risk factors, warning signs of respiratory disease, and prevention of post-TB complications, followed by screening using the modified Medical Research Council (mMRC) dyspnea scale and spirometry. Patients with serious respiratory complaints will get a consultation session with the pulmonologist. The activity was carried out from May to June 2025 and involved 50 patients who had completed 6 months of TB therapy. Results: Reported that participants presented with dyspnea of varying severity: mMRC 1–2 (18%), mMRC 3 (56%), and mMRC 4 (26%). Among these, 84% of patients with mMRC >2 had a history of extensive pulmonary lesions at initial diagnosis. Spirometry revealed that 94% of patients exhibited moderate to severe mixed obstructive-restrictive impairment. Conclusion: This study highlights the importance of screening for respiratory complaints after TB treatment, the early recognition of exacerbations, and the continuation of pulmonary rehabilitation in post-TB care.